PENGARUH PROFITABILITAS, LEVERAGE DAN DIVIDEN TERHADAP REAKSI PASAR - Magno, MelaniaAmaral Belo; Asyik, Nur Fadjrih (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is meant to examine the influence of profitability, leverage and dividend to the market reaction. The samples are 30 go public manufacturing companies which are listed in Indonesia Stock Exchange in 2010-2014 periods. The multiple linear regressionshas been applied as the statistic method to examine variables which influence stock price. The normality assumption test, multicolinearity, heteroscedasticity and autocorrelation show that there are variable differences so that the value of the stock price, profitability, divident and leverage becomes Log or Ln. The result of the research shows that partially the variables i.e. profitability and dividend have positive influence to the market reaction. It is shown by the result of t test of profitability variable is 2.140 with its significance 0.034 <0.05. Meanwhile, dividend variable is 10.176 with its significance of 0.000 <0.05. The leverage variable based on hypothesis test shows that it does not have any significant influence the market reaction. This is shown by the result of the t test is -0.683 with its significance is 0.495 > 0.05.Keywords: Profitability, Leverage, Divident, Market Reaction, Stock Price.